A poly (saccharide-ester-urethane) scaffold for mammalian cell growth - González-Torres, Maykel; Becerra-González, Marymar; Leyva-Gómez, Gerardo; Lima, Enrique; González Mendoza, Oswaldo; Ruvalcaba-Paredes, Erika Karina; Cortés, Hernán; Pineda, Carlos; Martínez-Torres, Ataúlfo (Cellular and Molecular Biology, 2021)
Chitosan and poly(3-hydroxybutyrate) are non-toxic, biodegradable, and biocompatible polymers extensively used in regenerative medicine. However, it is unknown whether the chemical combination of these polymers can produce a biomaterial that induces an appropriate cellular response in vitro in mammalian cells. This study aimed to test the ability of a novel salt-leached polyurethane scaffold of chitosan grafted with poly(3-hydroxybutyrate) to support the growth of three mammalian cell lines of different origin: a) HEK-293 cells, b) i28 mouse myoblasts, and c) human dermal fibroblasts. The viability of the cells was assessed by either evaluation of their capacity to maintain the expression of the green fluorescent protein by adenoviral transduction or by esterase activity and plasma membrane integrity. The results indicated that the three cell lines attached well to the scaffold; however, when i28 cells were induced to differentiate, they did not produce morphologically distinct myofibers, and cell growth ceased. In conclusion, the findings reveal that, altogether, these observations suggest that this foam scaffold supports cell growth and proliferation but may not apply to all cell types. Hence, one crucial question yet to be resolved is a poly (saccharide-ester-urethane) derivative with a nano-topography that elicits a similar cellular response for different biological environments.